2018
DOI: 10.2174/1570159x15666170424120802
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels as Novel Targets for Endogenous Ligands: Focus on Endocannabinoids and Nociceptive Signalling

Abstract: Background: Chronic pain is a significant clinical problem and a very complex pathophysiological phenomenon. There is growing evidence that targeting the endocannabinoid system may be a useful approach to pain alleviation. Classically, the system includes G protein-coupled receptors of the CB1 and CB2 subtypes and their endogenous ligands. More recently, several subtypes of the large superfamily of cation TRP channels have been coined as “ionotropic cannabinoid receptors”, thus highlighting their role in canna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 143 publications
0
48
0
Order By: Relevance
“…Furthermore, anandamide is an endogenous cannabinoid that controls appetite and energy balance, and is a selective endogenous TRPV1 partial agonist, i.e., its action on TRPV1 reduces pain 9 . Several studies have demonstrated important roles for the peripheral endocannabinoid system, including anandamide, in the regulation of energy metabolism.…”
Section: Potential Molecular Linksmentioning
confidence: 99%
“…Furthermore, anandamide is an endogenous cannabinoid that controls appetite and energy balance, and is a selective endogenous TRPV1 partial agonist, i.e., its action on TRPV1 reduces pain 9 . Several studies have demonstrated important roles for the peripheral endocannabinoid system, including anandamide, in the regulation of energy metabolism.…”
Section: Potential Molecular Linksmentioning
confidence: 99%
“…The transient receptor potential vanilloid type 1 (TRPV1) and transient receptor potential ankyrin-type1 (TRPA1) receptors are structurally related ligand-gated Ca 2+ permeable ion channels that are considered as an integral part of the ECS [38]. They are molecular integrators of a broad range of inflammatory stimuli including prostaglandins and AEA and play crucial roles in pain and inflammation [39].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%
“…Other components of the ECS are the transient receptor potential (TRP) channels, such as TRPV1, TRM8, and others (Storozhuk and Zholos, 2018). These receptors, widely expressed throughout the digestive tract, are involved in numerous processes: taste, chemo-and mechanosensation, thermoregulation, pain and hyperalgesia, mucosal function, gut homeostasis, and control of motility, amongst others (Kaneko and Szallasi, 2014).…”
Section: Irritable Bowel Syndrome and The Endocannabinoid System Endomentioning
confidence: 99%